Heavy Metal Toxicity to a Freshwater Crab, Barytelphusa cunicularis (Westwood) from Aurangabad Region - and G.K.Kulkarni, Atul R. Chourpagar (Recent Research in Science and Technology, 2011)
Pesticides of heavy metal salts are common pollutants of freshwater ecosystems where they induce adverse effects on the aquatic biota. Barytelphusa cunicularis is a key-species in Marathwada region having good nutritional value. Crabs live in close association with the sediment where accumulation of heavy metals pesticides is reported. Acute toxicity tests were conducted against the pesticides copper sulphate and mercuric chloride. Median Lethal Concentration (LC50) values of Copper sulphate were found to be 282, 258, 238 and 215 ppm respectively for 24, 48, 72 and 96 h., while those for mercuric chloride were 1.04, 0.84, 0.63 and 0.45 ppm respectively. This crab was found more sensitive to mercuric chloride than copper sulphate.